Effect of Modified Yarn Path Ring Spinning on Thermal Comfort Properties of Cotton Fabrics after Plasma Treatment. Issue 5 (4th May 2021) - Jebastin Rajwin, A.; Prakash, C.
ABSTRACT: The influence of air, oxygen and argon plasma treatment on the thermal comfort behavior of cotton woven fabric which is spun from modified yarn path in ring spinning has been investigated in this study. The cotton fabric samples were undergone different plasma treatment namely air, argon and oxygen. The fabric air permeability has tend to be decreased with the plasma treatment and the oxygen plasma-treated fabric has least air permeability. The untreated fabric shows higher air permeability followed by left diagonal yarn path, straight path and right diagonal yarn path. It was also observed thermal resistance and water vapor permeability of the fabric has increased with the plasma treatment and the oxygen plasma-treated fabric has higher thermal resistance and water vapor permeability. The untreated fabric shows lower thermal resistance and water vapor permeability followed by left diagonal yarn path, straight path and right diagonal yarn path.